Comparing INCOSE and PMI Portfolio Management Practices. Issue 1 (30th September 2020) - Specking, Eric; Parnell, Gregory S.; Pohl, Edward
Abstract: Many organizations use systems engineering and project management practices. In 2011, the International Council on Systems Engineering (INCOSE) and the Project Management Institute (PMI) announced a partnership to better integrate their practices and identified several common practices. This paper focuses on portfolio management by reviewing ISO/IEC/IEEE 15288 and key documentation from INCOSE and PMI. This paper 1) provides an overview of portfolio management; 2) identifies insights into portfolio management practices published by each organization; and 3) identifies areas that systems engineering organizations can enhance their portfolio management practices. We found that out of the total 2, 484 reviewed pages, 6.2% contained information on portfolio management. Additionally, PMI's The Standard for Portfolio Management contains the most portfolio management information, while INCOSE's Systems Engineering Body of Knowledge contained less information. Program and project management practices help ensure that organizations do programs and projects the "right" way, portfolio management help ensure they do the "right" programs and projects, and systems engineering ensures they use the "right" systems thinking. We conclude that INCOSE should adapt more of PMI's practices on portfolio management to help systems engineers improve their portfolio management practices.